Tingkat Pengetahuan Obat Bebas dan Obat Bebas Terbatas untuk Swamedikasi pada Masyarakat Perum Cengkong, Karawang: Knowledge Level of Over-the-Counter and Limited Over-the-Counter Drugs for Self-Medication Among the Community of Perum Cengkong, Karawang - Tyssa Mariyana; Weri Veranita; Ayu Fajariyani; Annisa Aliffiah Herawan (UIMA Press, 2024)
Knowledge of the correct medicine can certainly be said to be something important. With the right knowledge, people will be able to get the maximum benefit from the drug and can minimize all unwanted things that can occur due to the use of the drug. This study used purposive sampling and simple random sampling methods on certain variables. Data collection methods in this study include interviews and observations to obtain information about community knowledge. This study only aims to describe the object studied aims to determine the level of knowledge of the use of over-the-counter drugs and limited over-the-counter drugs in the public about knowledge of the use of over-the-counter drugs and limited over-the-counter drugs with the kiuisioner method found with good category results as many as 41 respondents (19%), for the sufficient category as many as 86 respondents (40%) and for the less category as many as 88 respondents (41%). This shows some correspondents who do not know about recognizing the signs of drug classes, how to get drugs, drug doses, drug indications, and how to store drugs.